Final answer:
To solve the equation y=ax-b for the variable x, add b to both sides and divide both sides by a.
Step-by-step explanation:
To solve the equation y=ax-b for the variable x, we can start by isolating the variable. In this equation, we have y=ax-b. To get rid of the -b term, we can add b to both sides of the equation: y+b=ax. Next, we can divide both sides by a to solve for x: (y+b)/a=x. To solve the equation y = ax - b for the variable x, we want to isolate x on one side of the equation. Here are the steps to do this:
Add b to both sides of the equation to get y + b = ax.
Divide both sides of the equation by a to get (y + b) / a = x.
So the solution for x in terms of y is x = (y + b) / a.
An example of this is the linear equation y = 9 + 3x. Here, the constant term is 9 and the slope is 3. This can be rearranged to x = (y - 9) / 3 by following the above steps.
Remember, slope and y-intercept are important components of a linear equation. In the form y = a + bx, b represents the slope, and a represents the y-intercept. To find x in terms of y, the process involves undoing what has been done to x, by reversing the operations applied to it in the equation.